Comparative study of oral mifepristone and endocervical prostaglandin-E2 gel as pre-induction cervical ripening agents in parturition - Dhillon, Prabhkiran; Biswas, Manash; Tripathi, Priyanka; Nair, Vinod G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Intracervical instillation of prostaglandin E2 is a well-known and widely practiced method of pre-induction cervical ripening. Mifepristone, due to its anti-progesterone action has been found to be a potential cervical ripening agent. This study was conducted to compare the safety, efficacy and outcome of these two drugs in pre-induction cervical ripening. Methods: One hundred antenatal women were recruited for the study; 50 in mifepristone arm and 50 in PG-E2 gel arm. Any singleton term pregnancy in vertex presentation with intact membranes and bishop’s score of <4 was included in the study. Any contraindication for vaginal delivery and any contraindication for mifepristone or PG-E2 were considered as exclusion criteria. Participants in the mifepristone arm were given tablet mifepristone 200 mg orally and those in PG-E2 gel group received endocervical instillation of PGE2 gel 0.5 mg, two doses 6 hours apart (if necessary). Induction of labour was considered successful if the parturient delivered within 48 hours of administration of mifepristone or first dose of PG-E2 gel, with or without labour augmentation with oxytocin. Delivery after 48 hours and caesarean delivery were considered unsuccessful induction. Results: There was a significant improvement in bishop’s score in mifepristone group 5.0±1.55 as compared to PG-E2 gel group 3.64±2.14; p value 0.001. Conclusions: Oral administration of 200 mg mifepristone is a safe, effective and convenient alternative to intracervical instillation of prostaglandin-E2 gel for pre-induction cervical ripening.